10 Management Considerations for Implementing an Endovascular Hybrid OR. (26th August 2014) - Eder, Sheryl P.; Register, Jennifer L.
Abstract: A hybrid procedure is the use of procedural techniques from different specialties to accomplish a shared procedural goal. Hybrid interventional suites combine the capabilities of an OR with the technologies of interventional radiology, thereby offering a modern solution to the care of patients with complex vascular pathology by using the least‐invasive procedure possible. Management considerations for successful implementation of an endovascular hybrid OR suite include environment of care, design, retrofitting, equipment, personnel, anesthesia, procedural care, radiation protection, and financial planning.